Efektivitas Pengembangan Sumber Daya Manusia pada Alumni STIBA Makassar - Muhammad Yunus, Imran; M. Dzul Fadli S; Farida Aprianti; Ridwan, Ridwan; Ahmad Amunir (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
This study aims to determine the effectiveness of human resource development, especially for STIBA Makassar alumni who are assigned to preach in various parts of Indonesia. This research is a field research using descriptive qualitative and descriptive quantitative methods through case study and phenomenological research approaches. Primary data sources are obtained directly from alumni as respondents and STIBA managers including stake holders as informants. The results showed that the development of human resources, especially STIBA Makassar alumni who were assigned to preach in various parts of Indonesia, was ineffective. This can be shown, both the overall effectiveness of the HR development program at 50.43% and specifically the effectiveness of all training at 52.2% and the effectiveness of all follow-up at 50.2%. This is certainly due to many causes and one of them is the effectiveness of the participation of follow-up participants of only 85.71% which is also in the less effective category. It is recommended that this overall effectiveness be improved in various ways. At least by having all trainees become follow-up participants.